Increasing Learning Motivation Based on Interactive Multimedia - Muhammad Feri Prasnanda (IAIN PAREPARE, 2025)
Background: Interactive multimedia is a learning media that integrates text, image, audio, and video elements in an integrated and interactive design to support the learning process. This study was motivated by the low motivation of students in learning diniyah. To overcome these problems, interactive multimedia is needed that can increase the attractiveness and effectiveness of learning. Research Objectives: To explore the application of Canva-based interactive multimedia in the learning process and identify its impact on students' learning motivation. This research used a qualitative approach with a case study method. The research was conducted at Madrasah Diniyah Hidayatul Mubtadiin Rembang using Canva-based learning media. Methods: The results showed that interactive multimedia increased learning motivation. The use of media that involves various senses makes the learning process more interesting and fun. The material presented through multimedia elements such as text, images, sound, animation, and video proved to facilitate understanding while fostering enthusiasm and active involvement of students in learning.